2020
DOI: 10.35326/jsip.v1i1.524
|View full text |Cite
|
Sign up to set email alerts
|

Efektifitas Penerapan Absensi Finger Print Terhadap Disiplin Pegawai Di Kantor Kecamatan Sorawolio Kota Baubau

Abstract: Pemanfaatan Teknologi Informasi menjadi salah satu daya dukung dalam proses pemerintahan, khususnya dalam penerapan absensi finger print untuk mengawasi kehadiran pegawai. Teknologi ini juga digunakan pada Kantor Kecamatan Sorawolio Kota Baubau, namun dalam implementasinya dianggap belum berjalan efektif dan efisisen. Penelitian ini mengkaji dampak penerapan model absensi finger print dan sejumlah faktor yang memengaruhinya. Tujuan dari penelitian ini adalah untuk mengetahui dampak penerapan absensi finger pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Absence is an activity or routine carried out by an employee to prove himself or herself present or not present at work in an agency. This absence relates to the application of discipline determined by each company or institution (Nani and Wijaya, 2020). According to respondents' perceptions, it was found that the effectiveness of member fingerprint attendance attendance can affect performance.…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…Absence is an activity or routine carried out by an employee to prove himself or herself present or not present at work in an agency. This absence relates to the application of discipline determined by each company or institution (Nani and Wijaya, 2020). According to respondents' perceptions, it was found that the effectiveness of member fingerprint attendance attendance can affect performance.…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…Some researchers stated that the fingerprint attendance system significantly influences employees' work discipline (Kamal, Winarso, and Hidayat, 2020); Nani & Wijaya (2020) ;Safudin, (2018). The findings contrast with Kusmayati, who stated that the fingerprint system only small impacts to the discipline, and the most significant factor is monitoring (Kusmayati, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Other factors that affect employee performance are electronic attendance and organizational culture. Several previous studies mention electronic attendance [4] [5][6] [7] and organizational culture [8] [9][10] also have a positive and significant influence on employee performance. The purpose of electronic attendance is to improve employee performance towards the organization which begins with discipline for employee attendance at work [11].…”
Section: Introductionmentioning
confidence: 99%
“…This study found a difference with previous research which lies in the research variables, where this study adds the independent variables of electronic attendance and organizational culture. The reason for adding this variable is because several previous studies have stated that electronic attendance [4][5][6] [7] and organizational culture [8][9][10] have a positive and significant influence on employee performance. The next difference is that the object of this research is an employee in the Banjar City Government Environment.…”
Section: Introductionmentioning
confidence: 99%